THE STUDY OF GROUNDWATER LEVEL RISE AND ITS RELATIONSHIP WITH FLOW DIRECTION AND SEAWATER INTRUSION IN ZLIT1EN CITY, LIBYA - Ashmila, Alhadi Ragab; Naji, Anwar O.; Abohamra, Ali Atiya; Abogamiza, Mohammed F.; Benzaghta, Mostafa A. (The 1st International Conference On Basic Sciences & Its Applictionss, 2024)
There has been an increase in the shallow groundwater level in the northern section of Zliten, which is 150 kilometers east of Tripoli, leading to higher levels than the surface of the land. The aim of this study was to characterize this phenomenon, ascertain the elevation of groundwater level relative to sea level, pinpoint the phenomenon's geographical borders, and identify regions vulnerable to its impacts. This was accomplished by gathering data from sixty shallow wells around the study area in order to investigate the geographical distribution of groundwater depth. Every well's location, water level, and ground surface height were noted and translated to sea level. The source of the salinity in the water was identified using the Simpson's ratio and the Jones ratio. The spatial distribution of chemical elements was mapped using ArcMap. The study finds out, groundwater migration is mostly directed northward, the most impacted locations saw a 0.0005 mm decrease in the piezometric surface slope, which added to the rise in water levels. The groundwater level rose to 4.25 meters above sea level, just 1200 meters from the ocean. Therefore, there was no correlation between the rise in water levels and seawater intrusion.
Keywords: Level rise; Seawater intrusion; Jones and Simpson ratio; Shallow water; Zliten